2015
DOI: 10.3382/ps/pev117
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary methionine content on growth performance, carcass traits, and feather growth of Pekin duck from 15 to 35 days of age

Abstract: A study was conducted to establish the response of Pekin ducks to dietary Met from 15 to 35 d age. Experimental diets were formulated to contain 0.35, 0.45, 0.55, 0.65, and 0.75% Met (0.30, 0.39, 0.45, 0.56, and 0.68% on an analyzed basis, respectively) and 0.3% cysteine (0.25, 0.27, 0.26, 0.26, and 0.28% on an analyzed basis, respectively). Each diet was fed to 10 pens of 55 ducks/pen. Carcass yields and feather growth were determined at 28 and 35 d. Results showed that feeding 0.30% Met (0.55% Met+Cys) signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 16 publications
(20 reference statements)
2
25
0
1
Order By: Relevance
“…Our results are in accordance with previous reports, where a linear unfavourable change of growth performance in ducks was found with increasing dietary RSM; this likely suggests that incremental increase of dietary RSM supplementation levels accompanied with higher dietary glucosinolates concentrations can have an exacerbated adverse impact on growth. Furthermore, feather growth is especially important economic trait for meat duck production (Zeng et al., ). In the current study, RSM impaired the growth of feather in ducks.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in accordance with previous reports, where a linear unfavourable change of growth performance in ducks was found with increasing dietary RSM; this likely suggests that incremental increase of dietary RSM supplementation levels accompanied with higher dietary glucosinolates concentrations can have an exacerbated adverse impact on growth. Furthermore, feather growth is especially important economic trait for meat duck production (Zeng et al., ). In the current study, RSM impaired the growth of feather in ducks.…”
Section: Discussionmentioning
confidence: 99%
“…During 8 to 12 weeks of age, in growing Muscovy ducks, no significant differences in growth performance were observed when CP-diet was reduced from 16 or 15 to 12% based on similar digestible amino acids such as methionine, lysine tryptophan and threonine, Baeza and Leclercq [22]. On the other hand, increasing dietary Met concentration from 0.30 to 0.68% improved bodyweight at 28-d and 35-d in growing Pekin ducks while decreased feed conversion ratio by 7.95% (p < 0.05) as a result of nutrient utilization, Zeng et al [23]. In the present study geese fed on high protein diets had better BW and FCR, which due to relatively high nutrient utilization comes from the nutritive value of diet riches in CP and TSAA especially Met which is an essential and first amino acid in poultry nutrition, and geese body can not synthesis it.…”
Section: Results Inmentioning
confidence: 98%
“…Within a certain range, the quality of feathers is directly proportional to the level of methionine. Zeng et al (2015) found that compared with that in the 0.45 and 0.56% methionine supplementation groups, the feather coverage of 35 days old ducks in the 0.30 and 0.39% methionine supplementation groups was significantly decreased, and the most suitable dietary methionine supplemental level was 0.484%. These results illustrated that sulfur-containing amino acids, which have been considered the first-limiting amino acids in most practical diets for poultry, play an important role in feather follicle development and feather growth.…”
Section: Amino Acidsmentioning
confidence: 87%
“…Importantly, feather follicle tissue is highly malleable, and dietary deficiencies can contribute to the obvious atrophy of the feather follicle, malformed feathers, fragile feathers, and feather loss. Dietary nutrition, especially crude proteins, amino acids, minerals, and vitamins, plays a key role in regulating the development of feather follicles and the growth of feathers (Supplee, 1966;Taylor, 1967;Urdaneta-Rincon and Leeson, 2004;Zeng et al, 2015). Therefore, it is important to dissect the effects of dietary nutrients on feather morphogenesis and the molecular mechanisms of feather follicle homeostasis.…”
Section: Nutrition and Feather Growthmentioning
confidence: 99%
See 1 more Smart Citation